2. Use the time-shifting property of the Fourier transform to show that if x(t) ←→ X(jw), then x(t + to) + x(t-to) ←→ 2x(ju) cos(tou). Use this result and the table of Fourier transforms in the textbook to find the Fourier trans- forms of the following two signals: ra(t) rb(t) -4 2 0 +2 +4 -4 2 0 +2 +4

image 350 - 2. Use the time-shifting property of the Fourier transform to show that if x(t) ←→ X(jw), then x(t + to) + x(t-to) ←→ 2x(ju) cos(tou). Use this result and the table of Fourier transforms in the textbook to find the Fourier trans- forms of the following two signals: ra(t) rb(t) -4 2 0 +2 +4 -4 2 0 +2 +4

This content is for Premium members only.
sign up for premium and access unlimited solutions for a month at just 5$(not renewed automatically)


images - 2. Use the time-shifting property of the Fourier transform to show that if x(t) ←→ X(jw), then x(t + to) + x(t-to) ←→ 2x(ju) cos(tou). Use this result and the table of Fourier transforms in the textbook to find the Fourier trans- forms of the following two signals: ra(t) rb(t) -4 2 0 +2 +4 -4 2 0 +2 +4

already a member please login